2015
DOI: 10.1373/clinchem.2014.236406
|View full text |Cite
|
Sign up to set email alerts
|

Overriding Concerns: The Role of Electronic Medical Record–Based Best Practice Alerts in Reducing Unnecessary Laboratory Testing

Abstract: In an era of rising healthcare costs and increasing emphasis on value-based healthcare spending, laboratory testing that is unnecessary, redundant, or otherwise wasteful is of increasing concern. Such testing may occur for myriad reasons including diagnostic uncertainty, defensive medicine, patient reassurance, or knowledge gaps regarding best practices. Whereas some studies have found the incidence of inappropriate laboratory testing to be as high as 95% (1 ), the true impact of laboratory overtesting is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Therefore, the EHR BPA linked to a separate REDCap database where the question could be answered honestly, assuaging regulatory concern. Separately, knowing BPA fatigue is well documented, we intentionally built the BPA as a pop-up, although users reported this feature was inhibitory on elicitation of barriers to physicians (32). Differential physician completion of the SQ may imply physicians were less likely to complete the question for patients for whom they felt the SQ was less applicable; reading the question may prompt some physicians to quickly assess prognosis, and triage completion of the REDCap only for those patients for whom they find the question applicable, arguably appropriately saving time by not documenting for patients they perceive to have a longer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the EHR BPA linked to a separate REDCap database where the question could be answered honestly, assuaging regulatory concern. Separately, knowing BPA fatigue is well documented, we intentionally built the BPA as a pop-up, although users reported this feature was inhibitory on elicitation of barriers to physicians (32). Differential physician completion of the SQ may imply physicians were less likely to complete the question for patients for whom they felt the SQ was less applicable; reading the question may prompt some physicians to quickly assess prognosis, and triage completion of the REDCap only for those patients for whom they find the question applicable, arguably appropriately saving time by not documenting for patients they perceive to have a longer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of unnecessary laboratory tests is even higher, because up to 95% of laboratory tests might be unnecessary. 12 A meta-analysis of 114 studies showed that about 20% of laboratory tests are ordered inappropriately. 8 Our intervention reduced the number of laboratory tests per patient, particularly in gynecology (by 68%).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, automated best practice alerts (BPAs) are increasingly being implemented in EHRs to flag patients who may be appropriate for screening or services and to enhance adherence to best practices. [20][21][22] EHR phenotypes such as those in this study can be incorporated into BPAs to identify patients in real time who may benefit from healthcare that is specific to the needs of latestage disease, including, but not limited to, palliative care.…”
Section: Discussionmentioning
confidence: 99%